Evaluasi Kesadaran Masyarakat terhadap Merek Produk Lokal Pada Perusahaan PT. The Tambi Indonesia - Mareta, Nurita Hera; Muslichah, Istyakara (SAFE-Network, 2024)
This research aims to determine brand awareness of the local product Tambi Tea among the people of Wonosobo Regency, which PT produces. Indonesian Tambi Tea. The background for this research is that there is a large distribution of local products in the Wonosobo Regency community, and it wants to assess how the Wonosobo community differentiates local products from conventional products. The research method used in this research is qualitative, and it is done by distributing several questionnaires and observations to consumers and related parties from the company. Observations are carried out during internship activities by identifying and evaluating existing issues in the company. Distribution of questionnaires to the people of Wonosobo Regency who have consumed Tambi Tea with an integrated approach through social media, relationship support and company assistance. This research assesses how the people of Wonosobo Regency differentiate between local products and conventional products, how the people of Wonosobo know about local Tambi tea products and the main reasons for purchasing local Tambi tea products. This research shows that the people of Wonosobo Regency are pretty aware of the presence of local products. It is hoped that in the future, Teh Tambi will use this as a company strength to promote local products further to the broader community.